Clinical Studies on HWANGRYUNHAEDOKTANG Herbal Acupuncture Therapy on Headache - Lee, Dae-Yong; Lee, Seung-Hoon; Kang, Hyung-Won; Lyu, Yeoung-Su; Jang, Hyun-Ho (Korean Pharmacopuncture Institute, 2003)
Objective: There are many treatments for headache. We suggested the clinical effect and utilization of HWANGRYUNHAEDOKTANG herbal acupuncture on headache. Methods: 1. We injected distillation of HWANGRYUNHAEDOKTANG(2.0cc) on Both Pung-Ji(GB20) of patients. In 20 minutes later, We examined therapeutic value of headache. 2. We examined effects of HWANGRYUNHAEDOKTANG Herbal acupuncture by sex , age, area of headache, period of history, degree of headache. Results and Conclusions: 1. There was a significantly effect of HWANGRYUNHAEDOKTANG Herbal acupuncture on headache. 2. In therapeutic value, The effect of HWANGRYUNHAEDOKTANG Herbal acupuncture by each type is significant.